A REVIEW OF THE UTTAR PRADESH POLITICAL PARTIES REGIONAL AND LOCAL LEVELS - Shikhar; Tiwari, Sandhya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the function and growth of local and regional political parties in Uttar Pradesh, emphasising their influence, governance-related effects, and historical development. In India, regional political organisations rose to prominence after 1967 as the Congress's hegemony waned, in contrast to national parties. The research looks at the main elements that led to the emergence of regional parties, as well as their organisational designs, election tactics, and influence on public policy. The study also looks at the region's shifting political landscape and voting patterns, showing how local political movements have impacted national politics. The report sheds light on the possibilities and difficulties various political parties in Uttar Pradesh confront by examining both historical patterns and recent advancements.